Kandungan Gizi dan Daya Terima Bakso Ikan Nila (Oreochromis niloticus) dengan Penambahan Tepung Labu Kuning (Cucurbita moschata) - Vicky Luvitasari Lumban Gaol; Etti Sudaryati; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Pumpkin (Cucurbita moschata) is the vines that serve as a source of provitamin A and antioxidants to the body. Tilapia fish (Oreochromis niloticus) is a freshwater fish that grow faster and have a high protein content. Both of these foodstuffs can be processed into food products one fish meatball that can provide and meet the nutritional needs the society. The purpose of this study was to determine the nutrient content and acceptance  of  fish meatballs with addition of pumpkin flour by oranoleptic analysis include color, flavor, taste and texture. This study was an experimental research making tilapia meatballs with a combination of pumpkin flour and tapioca flour with three treatment A1 (5%:10%), A2 (7,5%:7,5%) and A3 (10%:5%). Panelists in this study were students of Faculty of Public Health University of Sumatera Utara as many as 30 people and acceptance of test data were analyzed by Kruskal Wallis test. Organoleptic test research results obtained fish meatballs A2 preferably in terms of flavor, taste and texture, and fish balls A1 prefer from color. Based on analysis of Kruskal Wallis test with 95% confidence interval  is known that there is no difference in the effect of acceptance panelist for color, flavor, taste and texture on third treatment fish meatball. The result of the nutrient content of fish meatball A3 with the addition of 10 grams of pumpkin flour has protein 12,3gr, 290mg phosporus, 390,7mg calcium and 92,45 ppm betacaroten in 100 grams.This research recommended fish meatballs into a source of nutritious food on a toddler. Keywords: tilapia meatballs, pumpkin flour, acceptance test